Effect of Managerial Compensation and Leverage on Earnings Management: The Perspective of Agency Theory - Pasaribu, Siska Dentina (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to examine the effect of managerial compensation and leverage, proxied by the debt-to-asset ratio (DAR), on earnings management practices from an agency theory perspective. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2024. This research uses a quantitative approach with an associative design. Data were obtained from annual financial reports and corporate governance reports available on the official IDX website. The analysis technique used is multiple linear regression, with earnings management measurement using the Modified Jones Model. The results showed that simultaneously, managerial compensation and leverage have a significant effect on earnings management. However, partially, only managerial compensation has a significant effect on earnings management, while DAR has no significant effect. This finding confirms that compensation design influences management's tendency to manipulate earnings more than the company's debt structure. This finding suggests that financial incentives offered to management have a greater impact on encouraging earnings management practices than debt-based financing structures.